The Effectiveness of Orange Peel in Removing Nickel in Wastewater - Mohd Shapri, Nurul Syahirah (Universiti Teknologi PETRONAS, 2016)
Increasing of water pollution caused by nickel metal has led to a serious threat to public health. Besides, the conventional method to remove heavy metals in wastewater is found to be very expensive and not really effective. Adsorption of nickel ion using orange skin is found to be a suitable alternative for this problem. The aim of this project is to determine the effectiveness of orange peel to remove nickel in wastewater. In this project, a synthetic nickel solution with known nickel concentration was analysed with different contact time, initial concentration and adsorbent dosage. Langmuir and Freundlich isotherms were employed to explain adsorption equilibrium.